Reciclaje e integración patrimonial de un bien de interés cultural en el centro histórico de la ciudad de Villa de Leyva (Boyacá) caso de estudio: Claustro de San Francisco (2021)
The objective of this degree work is to carry out an investigation on the 6 facilities considered as a cultural asset in the historic center of the municipality of Villa de Nuestra Señora de Leyva, located in the Department of Boyacá. With the results of this investigation, proposes an intervention in heritage contexts for the recycling and integration of a property of cultural interest, the Cloister of San Francisco, in order to strengthen these facilities patrimonial of colonial character taking into account that they are very important for their history, both for the municipality and for Colombia.